2018
DOI: 10.1002/jmri.26592
|View full text |Cite
|
Sign up to set email alerts
|

MRI prognosticators for adverse maternal and neonatal clinical outcome in patients at high risk for placenta accreta spectrum (PAS) disorders

Abstract: Background Placenta accreta spectrum (PAS) disorders may be associated with significant mortality and morbidity for both mother and fetus. Purpose/Hypothesis To identify MRI risk factors for poor peripartum outcome in gravid patients at risk for PAS. Study Type Prospective. Population One hundred gravid women (mean age: 34.9 years) at third trimester, with placenta previa. Field Strength/Sequence T2‐SSTSE (single‐shot turbo spin echo), T2‐TSE, T1‐TSEFS (TSE images with fat‐suppression) at 1.5T. Assessment Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…This study also showed that the incidence of DIC in the PA group was higher, which may be related to the incidence of PPH and an insu cient endogenous supply of coagulation factors. In the present study, the incidence of puerperal infection and intraoperative bladder injury in the PA group was signi cantly increased (P<0.05), which is consistent with a previous report [32]. In addition, we found that the rate of hysterectomy, low birth weight, neonatal comorbidities, and time to NICU admission in the PA group were also signi cantly increased (P<0.05), which was consistent with the results of several previous investigations [23,33,34].…”
Section: Pregnancy Outcomes With Pasupporting
confidence: 92%
“…This study also showed that the incidence of DIC in the PA group was higher, which may be related to the incidence of PPH and an insu cient endogenous supply of coagulation factors. In the present study, the incidence of puerperal infection and intraoperative bladder injury in the PA group was signi cantly increased (P<0.05), which is consistent with a previous report [32]. In addition, we found that the rate of hysterectomy, low birth weight, neonatal comorbidities, and time to NICU admission in the PA group were also signi cantly increased (P<0.05), which was consistent with the results of several previous investigations [23,33,34].…”
Section: Pregnancy Outcomes With Pasupporting
confidence: 92%
“…It was reported that PAS disorders remained undiagnosed before delivery in half to two-thirds of cases [16,31]. Current prenatal diagnosis mainly rests on subjective interpretation of US and MRI ndings [16].US is the rst-level imaging modality to assess PAS disorders due to its convenience and lower cost [12,23]. However, it suffers from high operator-dependence and low reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical history of PAS disorders is considered as an e cient reference standard to be used in both research and clinical settings, that is, di cult manual, piecemeal removal of the placenta, absence of spontaneous placental separation 20 to 30 minutes after birth despite active management including bimanual massage of the uterus, use of oxytocin and controlled traction of the umbilical cord, retained placental fragment requiring curettage after vaginal birth and heavy bleeding from the placentation site after removal of the placenta during cesarean delivery [19,20 ]. It has good reliability and validity rates compared with other diagnostic standards, such as histopathology [5,12,21,22].…”
Section: Standard Of Referencementioning
confidence: 99%
See 1 more Smart Citation
“…During image interpretation, none of these MRI features are assessed in isolation, and the more the features that are identified, the greater the concern. Bourgioti et al (28) correlated specific MR features with clinical outcomes; and found that the presence of ≥ 3 MRI signs correlated with a complicated delivery, while ≥ 6 MRI signs were associated with massive bleeding, a hysterectomy, or extensive bladder repair.…”
Section: Step 4 Identify Risk Factors For Pas and Locate Placentamentioning
confidence: 99%